Implantação de trens logísticos em linhas de montagem de motores elétricos - Paris, Jean Cacio de (2017)
In the current scenario as companies that seek to excel in the world, they need to minimize the waste in their production processes. Seeking to reduce one of these wastes, the manufacturing time, a WEG company has been developing a study on an implementation of logistic trains (Mizusumashi) in its assembly plants. The main objective of this work is to identify how changes occurred with an implementation of Mizusumashi in an electric motors production unit of the company WEG and as specific objectives have been approached as the differences between the known production systems, present a methodology of work Toyota for an implementation of Mizusumashi and which ones as main preferences with this one. The implementation of the logistics train in the factory assembly line of engines began with a data collection, carried out with the data provided by the factory PCP and subsequent evaluation of different possible scenarios. With the histories were fixed in times of process, were obtained qualified for each of the logistic elements for the assembly line and which are routes to be made. After defining the chronometric tests formulation to define the time needed to supply the trains in the markets and the edges of data lines, which were used to determine the number of trains needed for each line. At the end of the implementation of Mizusumashi it was concluded that The pace of work became more balanced, the time available for an engine manufacturing had a better use than companies that previously did not add value to the final product were cut. The expenses with forklifts and the number of them working inside the factory were reduced, going from 7 to only 4 forklifts. Stock control has become easier and simpler. The implementation of Mizusumashi in Plant III proved to be of great value for the entire WEG company and served as a testing laboratory that was subsequently used to create documents with standards and guidelines for an implementation of the Mizusumashi process in other manufacturing plants. Validity or main objective of the present work. For sure this is just the beginning of a long walk of small conquests and better diaries that will not future bring great results.